Antenne Integrate Attive (2014)
Antenne Integrate Attive (“Active Patch Antennas”) represents the first issue of the series «Quaderni del Dottorato di Ricerca in Ingegneria dell’Informazione» ("Issues of the PhD course in Information Engineering”) of the University of Florence, used as a didactic support to the PhD course bearing the same name. Active patch antennas, object of the publication and introduced as the enabling technology for high performance multifunctional front-ends for radar and communication systems, are currently also being used for Personal Area Networks (PAN) and for Dedicated Short Range Communication (DSRC), at a low cost and power. In the arrays for space applications, where reliability is a key aspect, the approach to distributed active elements allows the improvement of the entire system’s defect tolerance. The issue is organized into six chapters. The first three chapters present the basic concepts related to radio links, the definition of the used parameters and their involvement in the constitutive relationships. In the fourth and fifth chapters, the design methods of the main antenna configurations are discussed, and some examples of application are provided. Finally, chapter six reviews the analysis methods used in modern software for electromagnetic and microwave circuit simulation.